Invasive fungal infection caused by geotrichum capitatum in patients with acute lymphoblastic leukemia: a case study and literature review - Gao, Guang-Xun (Int J Clin Exp Med, 2015)
Geotrichum capitatum infection has a very low incidence rate with atypical clinical symptoms, making diagnosis difficult, and it has a poor prognosis. The incidence is even more rare in China. This paper reports the first case of infection caused by G. capitatum during bone marrow suppression after chemotherapy in a Chinese patient with acute lymphoblastic leukemia. In addition, it reports a systematic literature review of diagnosis and treatment. The patient with acute lymphoblastic leukemia was confirmed to be infected with G. capitatum, involving lung, liver and skin, through a blood culture test. Caspofungin, amphotericin B loposome, and a combination therapy of amphotericin B liposome and voriconazole were used in succession for treatment. Despite normal body temperature and a slight improvement of clinical symptoms with the combination therapy treatment, the patient died 40 days after chemotherapy due to heart and lung failure.